Oppositional voting in the Council of the EU between 2010 and 2019: Evidence for differentiated politicisation. (September 2021) - Pircher, Brigitte; Farjam, Mike
This article presents a new and previously unchartered dataset on roll call votes for all 28 member states in the Council of the EU between 2010 and 2019 and studies the effects of politicisation on governments' oppositional voting in the different policy areas. We contribute to the literature with two main findings. First, our study provides strong evidence for bottom-up politicisation, where Euroscepticism and the left-right positions of national political parties strongly affect governments' voting in the Council. Second, we provide new evidence for a form of differentiated politicisation where ideological standpoints of political parties in government and opposition have different effects on oppositional voting in the various policy areas.